Pengaruh Tingkat Inflasi Dan Pendapatan Usaha Pegadaian Terhadap Pembiayaan Rahn Pada Pegadaian Syariah Tahun 2011-2020 - Siti Aisah; R. Deden Adhianto; Putri Anjelli (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2021)
In deciding the provision of rahn financing, it is influenced by various conditions, especially internal and external conditions. These internal factors or conditions include the development of pawnshop business income. Meanwhile, external conditions or factors can be seen from the financial conditions that occur in Indonesia, for example the inflation rate. This study aims to determine the effect of inflation rate and operating income on rahn financing at Islamic pawnshops in Indonesia partially and simultaneously. This research was conducted at a non-bank financial institution, namely PT. Pawnshops that focus on sharia segmentation. This type of research uses a quantitative descriptive method that is associative. The secondary data used in this study used a documentation study data collection technique. This research uses multiple linear regression data analysis method. Based on the results of the analysis and discussion of the data in this study, it is stated that the first tcount is -0.030, meaning that ttable is greater than tcount (2.365 > -0.030) and sig.0.977 > 0.05. From these results, inflation has a negative effect and inflation does not have a significant effect on the financing of rahn partially. Second, the results of the tcount value on the operating income variable produce a tcount of 7.141, meaning that tcount is greater than ttable (7.141 > 2.365) and a significant value of 0.000 < 0.05. From these results, it means that operating income has a positive effect and pawnshop income has a significant effect on Rahn's financing partially. The results of the simultaneous test (f test) obtained a ftable value of 4.46 because the fcount value of 38,698 is greater than the ftable value and the significance value of 0.000 is much smaller than 0.05. So it can be concluded that the inflation variable and Pawnshop income simultaneously affect the rahn financing variable at the Indonesian Sharia Pawnshop. And the relationship between the independent variable and the dependent variable in this study was 0.893 or 89.3%, while 10.7% was explained by other factors not presented in this study.